Persistent pollutants exceed toxic thresholds in a freshwater top predator decades after legislative control. (1st March 2021) - Kean, E.F.; Shore, R.F.; Scholey, G.; Strachan, R.; Chadwick, E.A.
Abstract: Declining emissions of persistent organic pollutants (POPs), subject to international control under the Stockholm convention, are not consistently reflected in biotic samples. To assess spatial and temporal variation in organochlorine pesticides and PCBs in UK freshwaters, we analysed tissues of a sentinel predator, the Eurasian otter, Lutra lutra between 1992 and 2009. Past declines in otter populations have been linked to POPs and it is unclear whether otter recovery is hampered in any areas by their persistence. PCBs, DDT (and derivatives), dieldrin and HCB were detected in over 80% of 755 otter livers sampled. Concentrations of ∑PCB, ∑DDT and dieldrin in otter livers declined across the UK, but there was no significant time trend for ∑PCB-TEQ (WHO toxic equivalency, Van den Berg et al., 2006) or HCB. In general, higher concentrations were found in the midlands and eastern regions, and lowest concentrations in western regions. Concentrations of PCBs and HCB in otters increased near the coast, potentially reflecting higher pollutant levels in estuarine systems. Decades after legislative controls, concentrations of these legacy pollutants still pose a risk to otters and other freshwater predators, with spatially widespread exceedance of thresholds above which reproduction or survival has been reduced in related species. Graphical abstract: Image 1 Highlights: Decades after control, POPs remain above toxic thresholds in many otters. Dieldrin, DDT and most PCBs are declining, but HCB and PCB-TEQ are not. Concentrations may limit reproduction in some areas of the UK. Developmentally vulnerable juveniles show the highest concentrations. Abstract : Dieldrin and DDT have declined in UK otters since the early 1990s, but HCB has not; PCBs frequently exceed toxic thresholds associated with reproduction in a related species.